Pediatric massage in conjunction with other traditional Chinese medicine therapies for tic disorder in children: systematic review and network meta-analysis - Liu, Jiayue; Zhang, Hanyu; Yu, Tianyuan; Chen, Jinping; Zhang, Yingqi; Sun, Jiawei; Xu, Yue; Na, Rentuya; Yan, Jiawang; Zhang, Hongzheng; Lu, Mengqian (Frontiers in Pediatrics, 2025)
BackgroundPediatric massage (PM) belongs to traditional Chinese medicine treatment (TCM) and is an alternative therapy for tic disorders (TD). This systematic review and network meta-analysis (NMA) was undertaken to evaluate the efficacy and safety of PM, the effectiveness of PM in conjunction with other TCM therapies for TD and to provide an evidence-based foundation for the clinical selection of the TD treatment regimens relating to traditional Chinese medicine.MethodsEight databases were systematically searched from their inception to June, 2024 for randomized controlled trials (RCTs) of PM and its combination with other TCM therapies for TD. Two researchers screened the studies and extracted the data according to our inclusion criteria, and the bias assessment tool from the Cochrane Handbook was used to evaluate the quality of the included studies. Stata 17.0 software was used to perform NMA, and the efficacy and safety of PM and its combination with other TCM therapies were compared and ranked.ResultsA total of 24 RCTs, covering 1,657 children with TD, were included in this NMA. There were 9 intervention measures, including PM, Western medicine (WM), PM + Chinese herbal medicine (CHM), PM + manual acupuncture (MA), PM + auricular acupuncture (AA), PM + Qigong therapy (QT), PM + cupping therapy (CT), PM + scraping therapy (ST), and PM + moxibustion (Mox). PM + CHM may be most effective at improving the total effective rate and decreasing YGTSS motor tics score and YGTSS vocal tics score; PM + MA may have the best performance in reducing the YGTSS total score; and simple PM may be the best at reducing the adverse reaction rate. The GRADE assessment showed that the overall response rate and the total YGTSS score were rated as low or very low quality due to the limitations of the original study, and other measures were rated as moderate quality. Therefore, these results need to be interpreted with caution and validated further.ConclusionPM and its combination with other TCM therapies are effective and safe interventions for TD in children. More specifically, PM + CHM may be the best choice for improving clinical effectiveness and reducing YGTSS motor tics score and YGTSS vocal tics score, while PM + MA may be the most effective for decreasing YGTSS total score. However, due to the limitations of this study, these conclusions still need to be validated using additional high-quality RCTs.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024553846, PROSPERO CRD42024553846.